2021
DOI: 10.1016/j.jbc.2021.100520
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages bind LDL using heparan sulfate and the perlecan protein core

Abstract: The retention of low-density lipoprotein (LDL) is a key process in the pathogenesis of atherosclerosis and largely mediated via smooth-muscle cell-derived extracellular proteoglycans including the glycosaminoglycan chains. Macrophages can also internalize lipids via complexes with proteoglycans. However, the role of polarized macrophage-derived proteoglycans in binding LDL is unknown and important to advance our understanding of the pathogenesis of atherosclerosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 72 publications
2
20
0
Order By: Relevance
“…M2 macrophages are far away from the lipid core of plaque, and primarily distributed in the stable area of the plaque. M2 macrophages possess a solid ability to remove lipids by phagocytosis (Ng et al, 2021). They can secrete anti-inflammatory cytokines (such as IL-10, TGF-β) to help wound healing, which plays a significant role in tissue repair.…”
mentioning
confidence: 99%
“…M2 macrophages are far away from the lipid core of plaque, and primarily distributed in the stable area of the plaque. M2 macrophages possess a solid ability to remove lipids by phagocytosis (Ng et al, 2021). They can secrete anti-inflammatory cytokines (such as IL-10, TGF-β) to help wound healing, which plays a significant role in tissue repair.…”
mentioning
confidence: 99%
“…Though SMCs are the major source of proteoglycan secretion in the intima, macrophages can also secrete proteoglycans that contribute to lipoprotein retention ( Kolset and Gallagher, 1990 ; Wight, 2018 ; Ng et al, 2021 ). For example, macrophages synthesize chondroitin sulfate proteoglycans, which connect atherogenic LDL and SRA in proximity, promoting more lipoprotein uptake and foam cell development ( Christner, 1988 ; Santiago-García et al, 2003 ).…”
Section: Mediators and Regulation Of Macrophage Foam Cell Formationmentioning
confidence: 99%
“…Analysis of macrophage conditioned medium showed that macrophage colony-stimulating factor (MCSF) could complex with proteoglycans when secreted by macrophages, which promoted monocyte differentiation and lipoprotein retention at the same time, contributing to foam cell development ( Chang et al, 1998 ) . Recently, Ng and colleagues also identified that perlecan was the major proteoglycan secreted by human macrophages involved in LDL retention, though perlecan was also suggested to be low in human lesions ( Tran et al, 2007 ; Ng et al, 2021 ). It was observed that proteoglycan synthesis by macrophages was upregulated when macrophages received inflammatory stimuli or were under hypoxia stress.…”
Section: Mediators and Regulation Of Macrophage Foam Cell Formationmentioning
confidence: 99%
“…The retention ability of proteoglycans is mainly addressed in the context of SMCs and endothelial cells. However, macrophage-derived proteoglycans notably also bind lipoproteins via both their protein core and heparan sulphate GAG chains [ 7 ▪▪ ]. In the same study, the authors reported that the matrisome of macrophages is sensitive to macrophage polarization.…”
Section: Proteoglycans and Their Glycosaminoglycans In Atherosclerosismentioning
confidence: 99%
“…In support of these observations, it was reported that HS biosynthesis is fine-tuned during macrophage polarisation, depicting their resolving or proinflammatory macrophage phenotype during atherosclerosis-related inflammation [ 21 ]. Recently, it was reported that M1 macrophages produced PGs with a higher level of HS chain sulphation compared with M2 macrophages [ 7 ▪▪ ]. These observations encourage further studies on the significance of HS in the immune signature of the plaques that may lead to future improved treatment against plaque destabilization.…”
Section: Proteoglycans and Their Glycosaminoglycans In Atherosclerosismentioning
confidence: 99%